ANALISIS SELF EFFICACY SISWA PADA PEMBELAJARAN EKONOMI DI KELAS X IPS 2 MAN 2 PONTIANAK - Lestari, Dia Ayu; Genjik, Bambang; Warneri, Warneri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract The title of the research is analysis of students self efficacy in economic learning at class X IPS 2 MAN 2 Pontianak. This study aims to determine students self-efficacy in economic learning at class X IPS 2 MAN 2 Pontianak. This research is based on the finding of the problem when researcher did observation about students self-efficacy during economic learning. The research method used is descriptive method with a qualitative approach and the research form is survey. Sources of data in this study were students of class X IPS 2, totaling 35 students and teacher of economic subjects. Data collection is obtained by observation results and interview results, then analysis using data reduction, data presentation, and verification / conclusion based on students affective success based on comparison of numbers (percentages) and predicates, then checking the validity of the data using triangulation techniques. Researcher conducted this study by conducting  observations 3 times and interviews 4 times.  The results show that the mastery experience and the vicarious expereience in the development of students self-efficacy can be said to be poor, the verbal persuasion in the development of students self-efficacy can be said to be quite good while the physiological state in the development of self-efficacy of students can be said to be not good. Keywords: Mastery Experience, Vicarious Experience, Verbal Persuasion, Physiological State